SHANK3 gene: Genotype-Phenotype relationship in a sample with Autism spectrum disorder and/or Intellectual Developmental Disability - Carreira, Maria Inês da Conceição (2020)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina